Analisis Semiotika Dalam Meme Politik Yang Diunggah Oleh Akun Tik Tok @bem.ui - Sukmana, Dinastisya; Claretta, Dyva (Jurnal Ilmiah Wahana Pendidikan, 2023)
The presence of social media is a form of technological advancement in the era of gloalization. This novelty makes people carry out their activities in a new way. Social media also has the power to make people dare to express opinions. Memes are a form of expressing opinions that are often found on social media. The Job Creation Law is a phenomenon that causes cons in society. Political memes were then present on one of the social media, namely Tik Tok uploaded by one of the BEM UI student organizations. The purpose of this study is to find out the signs in memes and know the overall message or meaning in the meme. This study used descriptive qualitative research methods and involved semiotic analysis methods by Charles Sanders Pierces. The object of this study is a political meme uploaded by the Tik Tok account @bem.ui in March 2023 Based on the results of the analysis, in the meme there are signs and objects that have a in the meme there are signs and objects that have implied meanings and messages.